2007
DOI: 10.1126/science.1147248
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Pentapeptide Is a Quorum-Sensing Factor Required for mazEF -Mediated Cell Death in Escherichia coli

Abstract: mazEF is a toxin-antitoxin module located on many bacterial chromosomes, including those of pathogens. Here, we report that Escherichia coli mazEF-mediated cell death is a population phenomenon requiring a quorum-sensing molecule that we call the extracellular death factor (EDF). Structural analysis revealed that EDF is a linear pentapeptide, Asn-Asn-Trp-Asn-Asn. Each of the five amino acids of EDF is important for its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
266
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(274 citation statements)
references
References 25 publications
7
266
1
Order By: Relevance
“…The quorum sensing peptide designated Extracellular Death Factor (EDF), originally described by Kolodkin-Gal et al, is responsible for the mazEF and chpBIK-mediated cell death in Escherichia coli. This intestinal commensal bacterium synthesizes this EDF peptide during logarithmic growth stages when stress-situations are induced [23,24]. Our study now enlarges the role of EDF to mammalian cells.…”
Section: Epithelial To Mesenchymal (Emt)-like Transition and Relatedsupporting
confidence: 52%
“…The quorum sensing peptide designated Extracellular Death Factor (EDF), originally described by Kolodkin-Gal et al, is responsible for the mazEF and chpBIK-mediated cell death in Escherichia coli. This intestinal commensal bacterium synthesizes this EDF peptide during logarithmic growth stages when stress-situations are induced [23,24]. Our study now enlarges the role of EDF to mammalian cells.…”
Section: Epithelial To Mesenchymal (Emt)-like Transition and Relatedsupporting
confidence: 52%
“…A recent paper showed that bacterial communication, through indole signaling in stationary phase, also induces an increase in which might benefit the surrounding clonal population. 20 This is dependent on cell density via a quorum sensing-like signal (extracellular death factor/EDF 51 ). An interesting recent report demonstrated that MazF cleaves to remove the 3' end of 16S rRNA containing the anti-Shine-Dalgarno sequence, thus committing a fraction of the ribosomes to the translation of leaderless mRNAs.…”
Section: Stochastic or Deterministic Generation Of Persisters?mentioning
confidence: 99%
“…We deduced 23 new sequences from the zwf alignment of EDF. In addition to these sequences, we synthesized three amidated forms that might be present in vivo as was described for the original EDF (Kolodkin-Gal et al 2007). Together with the known EDF peptide from E. coli NNWDN and its in vivo amidated form NNWNN, this resulted in a library of in total 29 EDF peptide variants (Table 2).…”
Section: Resultsmentioning
confidence: 99%